Prevalence of Proteus spp. in some hospitals in Baghdad City - Azher Ahmed, Dalia (Iraqi Journal of Science, 2023)
In this research, 152 clinical samples were collected from different hospitals inBaghdad city, 30 isolates of Proteus spp. were identified from urine, wounds andburns by using different bacteriological and biochemical assays. It was found that 20(66.6%) samples were identifies as Proteus mirabilis and 10 (33.3%) samples wereProteus vulgaris. Among the 30 isolates of Proteus spp., 18 isolates (60%) wereisolated from urine samples; 7 (23.3%) isolates from wounds samples and 5 (16.6%)isolates from burns samples. Out of 20 isolates of P. mirabilis, 13 (65%) isolateswere from urine samples, 4 (20%) isolates were isolated from wounds samples and 3(15%) isolates from burns. According to the gender, out of 30 Proteus spp., 17(56%) were from female and 13 (43%) from male at different age.